Integrating ESG Criteria in Corporate Strategies: Determinants and Implications for Performance - Alhoussari, Houda (Journal of Ecohumanism, 2025)
This study explores the integration of Environmental, Social, and Governance (ESG) principles into corporate practices, focusing on the methodologies used for their evaluation and the factors influencing their adoption. Through a qualitative and comparative analysis of European and Saudi Arabian contexts, the research examines how companies align their strategies with ESG requirements in diverse regulatory and cultural environments. Data is drawn from established ESG rating agencies, corporate sustainability reports, and case studies, allowing for a thorough investigation of internal and external evaluation processes and their implications for ESG scores. The study identifies key challenges in ESG implementation, including ambiguities in definitions, resource disparities, sector-specific considerations, and resistance due to cost or unfavorable ratings. It also highlights the role of legal and regulatory frameworks, such as the ESG Disclosure Guidelines introduced by the Saudi Capital Market Authority and global standards like the Global Reporting Initiative (GRI), in shaping corporate ESG practices. Recommendations emphasize the need for standardized evaluation criteria, targeted support for smaller enterprises, and stronger legal frameworks to promote transparency and compliance. The findings contribute to a deeper understanding of ESG dynamics and provide actionable insights for advancing corporate sustainability on a global scale.